NC-AFM and XPS Investigation of Single-crystal Surfaces Supporting Cobalt (III) Oxide Nanostructures Grown by a Photochemical Method - Mandia, David J. (Université d'Ottawa / University of Ottawa, 2012)
The work of this thesis comprises extensive Noncontact Atomic Force Microscopy (NC-AFM) characterization of clean metal-oxide (YSZ(100)/(111) and MgO(100)) and graphitic (HOPG) supports as templates for the novel, photochemically induced nucleation of cobalt oxide nanostructures, particularly Cobalt (III) Oxide. The nanostructure-support surfaces were also studied by X-ray Photoelectron Spectroscopy (XPS) to verify the nature of the supported cobalt oxide and to corroborate the surface topographic and phase NC-AFM data. Heteroepitaxial growth of Co2O3 nanostructures proves to exhibit a variety of different growth modes based on the structure of the support surface. On this basis, single-crystal support surfaces ranging from nonpolar to polar and atomically flat to highly defective and reactive were chosen, again, yielding numerous substrate-nanostructure interactions that could be probed by high-performance surface science techniques.
Keywords: Physical Chemistry; Surface Physics; Surface Chemistry; Physics; Chemistry; Inorganic Chemistry; Electrochemistry; X-ray Photoelectron Spectroscopy; Atomic Force Microscopy; Metal Oxides; Scanning Probe Microscopy